The Liability of Criminal Law towards a Notary Official in the Crime of Embezzlement at the Denpasar District Court - Simon Nahak (Warmadewa Press, 2020)
This study aims to investigate three issues namely the legal consequences of Criminal Acts against Victims of Misappropriated Crimes by a Notary Officer, the factors cause a Notary Officer to commit a Criminal Act in the Legal District of the Denpasar District Court and the qualifications of criminal acts, responsibilities and formulations Criminal system for the perpetrators of embezzlement by a notary at the Denpasar District Court. The method used is Normative Juridical collaboration method with Empirical Juridical. The techniques of data collection is interview. The results show that criminal law consequences of perpetrators and victims of embezzlement crimes by a notary officer is that the perpetrators must be held accountable for their actions legally, whereas victims who suffer losses due to criminal acts are processed to be given criminal sanctions through the criminal justice process at the Denpasar District Court. Then, factors causing crime that are internal and external factors. There are some external factors, namely ​​residence factor, economic factor, political factor and legal system factor. Furthermore, the forms of embezzlement are included in the forms/qualifications of types of non-violent acts, embezzlement criminal responsibility is an individual criminal liability not a legal entity, the system of punishment against perpetrators of embezzlement is the application of criminal law sanctions through the criminal justice process so that against the crime of embezzlement convicted of committing sanctions in the form of imprisonment and fines.